Analisis Determinan Karakteristik Individu Tenaga Keperawatan dengan Kepuasan Kerja di Ruang Rawat Inap Rumah Sakit Umum dr. H. Koesnadi Bondowoso (Analysis Determinants of Individual Characteristics Nursing Staff with Job Satisfaction in The Patient Unit - Moh Taufiqurrahman; Nurfika Asmaningrum; Retno Purwandari (Pustaka Kesehatan, 2014)
Job satisfaction is a part of the embodiment of the working attitude that is believed to bringinfluence on work behavior. Job satisfaction is an affective reaction to the work is theresult of a comparison of what is happening now and what is actually expected. The studypurpose is to analyze the determinants of individual characteristics and job satisfaction ofnurses in the inpatient of dr. H. Koesnadi’s Hospital Bondowoso. The results of the studyknown that the nursing staff had problems on the job satisfaction salary, promotion, andsupervision. Using analytical observational research with cross sectional approach. Thesampling technique used in this study is purposive sampling. The population research wasnursing staff in the inpatient unit. There are 73 samples of nursing staff. The instrumentused in this research was a questionnaire. The conclusion from the research is that thereare two characteristics of individuals who are relationship with job satisfaction is nogender relations and the position and job satisfaction in the inpatient unit of dr. H.Koesnadi’s Hospital Bondowoso.Keywords: individual characteristics, job satisfaction, nursing services